2011
DOI: 10.1039/c1lc00001b
|View full text |Cite
|
Sign up to set email alerts
|

A low-voltage electrokinetic nanochannel drug delivery system

Abstract: Recent work has elucidated the potential of important new therapeutic paradigms, including metronomic delivery and chronotherapy, in which the precise timing and location of therapeutic administration has a significant impact on efficacy and toxicity. New drug delivery architectures are needed to not only release drug continuously at precise rates, but also synchronize their release with circadian cycles. We present an actively controlled nanofluidic membrane that exploits electrophoresis to control the magnit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 63 publications
2
32
0
Order By: Relevance
“…At a higher applied voltage, stronger electric fields led to a larger MB electrophoretic motion, resulting in a steeper slope in transient MB release profile. The slope, or the release rate, jumped from 0.19 lg/h at 1.5 V to 0.97 lg/h at 3.5 V. These release rates were roughly of the same order as those reported by Fine et al, 21 but with a slightly higher voltage. The transient MB release profiles can be described by Eq.…”
Section: A Electrophoretic Release Mechanismsupporting
confidence: 73%
See 1 more Smart Citation
“…At a higher applied voltage, stronger electric fields led to a larger MB electrophoretic motion, resulting in a steeper slope in transient MB release profile. The slope, or the release rate, jumped from 0.19 lg/h at 1.5 V to 0.97 lg/h at 3.5 V. These release rates were roughly of the same order as those reported by Fine et al, 21 but with a slightly higher voltage. The transient MB release profiles can be described by Eq.…”
Section: A Electrophoretic Release Mechanismsupporting
confidence: 73%
“…Among them, pulsatile drug delivery systems (PDDS) have drawn attention as they allow repeatable and reliable drug release flux for clinical needs. Further, external stimulation signals such as temperature variation, 9,10 magnetic fields, [11][12][13][14] and electric fields, [15][16][17][18][19][20][21] can be used in PDDS to trigger or control drug release rates, thereby allowing remote control of local drug administration. Most of the PDDS devices are composed of a drug-loading container covered with a functional membrane, with drug release rates through the functional membrane controlled by modulating the external stimulations.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in a previous study with 100 nm nanochannels, 21 the results observed with 1 μm channel membranes showed a very different response to the applied potential than the smaller nanochannels. A decrease in DF-1 release rate with respect to the passive trend was observed at negative bias (-1.5 V), while an increase of approximately 20% was produced with a positive bias of 2 V (polarity reversed).…”
Section: Resultssupporting
confidence: 52%
“…As one of the promising nanofluidic components, they have been used in various fields, like biosensing,1 energy conversion,2 drug delivery,3 and so on. Until now, substantial studies on the construction of nanochannels have focused on the interior surface modifications because unique ionic transport behaviors usually originate from the interactions between ions and surface charges or groups in nanoconfined spaces 4.…”
Section: Introductionmentioning
confidence: 99%